Surface laser treatment of cast irons: A Review - Catalán, Néstor (2022)
Heat treatments are frequently used to modify the microstructure and mechanical properties of materials according to the requirements of their applications. Laser surface treatment (LST) has become a relevant technique due to the high control of the parameters and localization involved in surface modification. It allows for the rapid transformation of the microstructure near the surface, resulting in minimal distortion of the workpiece bulk. LST encompasses, in turn, laser surface melting and laser surface hardening techniques. Many of the works devoted to studying the effects of LST in cast iron are diverse and spread in several scientific communities. This work aims to review the main experimental aspects involved in the LST treatment of four cast-iron groups: gray (lamellar) cast iron, pearlitic ductile (nodular) iron, austempered ductile iron, and ferritic ductile iron. The effects of key experimental parameters, such as laser power, scanning velocity, and interaction time, on the microstructure, composition, hardness, and wear are presented, discussed, and overviewed. Finally, we highlight the main scientific and technological challenges regarding LST applied to cast irons.